Refractory kawasaki disease after dpt vaccination: A case report and literature review - Subhadarsini, Santoshi; Narayani, Vani; Anwar, Saba; Baghel, Sudhir; Deswal, Shivani; Dewan, Vivek (Indian Journal of Case Reports, 2019)
The etiology and pathogenesis of Kawasaki disease (KD) remain poorly understood. Among the diverse infectious and environmental factors examined to be triggers for, or be associated with, KD, are immunizations. We are reporting a case of refractory Kawasaki disease after DPT booster in a 5-year-old male child, who responded after two doses of IVIG and a course of IV Methylprednisolone. Prior published case reports and large epidemiological studies, which explore potential associations between immunization and KD, are also comprehensively reviewed.